2015
DOI: 10.1186/s12967-015-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

GLI2 inhibition abrogates human leukemia stem cell dormancy

Abstract: BackgroundDormant leukemia stem cells (LSC) promote therapeutic resistance and leukemic progression as a result of unbridled activation of stem cell gene expression programs. Thus, we hypothesized that 1) deregulation of the hedgehog (Hh) stem cell self-renewal and cell cycle regulatory pathway would promote dormant human LSC generation and 2) that PF-04449913, a clinical antagonist of the GLI2 transcriptional activator, smoothened (SMO), would enhance dormant human LSC eradication.MethodsTo test these postula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 53 publications
2
78
0
Order By: Relevance
“…It was previously reported that Hh signaling modulates cell cycle regulators in stem cells to control normal hematopoietic regeneration . In the BCR‐ABL‐positive leukemia model, selective SMO inhibition abrogates human LSC dormancy . The authors showed that treatment with PF‐913 in humanized stromal cocultures reduced downstream cell cycle gene expression and sensitized BCR‐ABL‐positive LSCs to tyrosine kinase inhibition.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It was previously reported that Hh signaling modulates cell cycle regulators in stem cells to control normal hematopoietic regeneration . In the BCR‐ABL‐positive leukemia model, selective SMO inhibition abrogates human LSC dormancy . The authors showed that treatment with PF‐913 in humanized stromal cocultures reduced downstream cell cycle gene expression and sensitized BCR‐ABL‐positive LSCs to tyrosine kinase inhibition.…”
Section: Discussionmentioning
confidence: 96%
“…(27) In the BCR-ABL-positive leukemia model, selective SMO inhibition abrogates human LSC dormancy. (28) The authors showed that treatment with PF-913 in humanized stromal cocultures reduced downstream cell cycle gene expression and sensitized BCR-ABL-positive LSCs to tyrosine kinase inhibition. A recent study also reported that inhibition of Hh signaling induced apoptosis by decreasing c-Myc protein expression in OPM1 myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Glasdegib prevents the translocation of SMO into primary cilia and prevents SMO‐mediated activation of downstream Hh targets . Previous studies have reported glasdegib inhibition of SMO reduced the expression of key intracellular leukemia stem cell regulators (eg, GLI2) and enhanced cell cycle transit . These results and preclinical evidence that Hh inhibition may sensitize cells to cytarabine or azacitidine provided rationale for evaluating glasdegib in combination with chemotherapeutic agents to reduce resistance and leukemic persistence or progression.…”
Section: Introductionmentioning
confidence: 84%
“…CSCs, represent a rare population of cells amongst the tumor bulk that are able to maintain the tumor via proliferation and self-renewal 13 capabilities and telomerase expression 13 . They are also known to be more resistant to conventional treatment (chemotherapy and radiotherapy) and responsible for cancer relapse and metastasis 14,15 . Their quiescent state and specific interactions with their microenvironment play a significant role in their drug resistance properties 16 .…”
Section: ) Cancer Stem Cells and Their Role In Tumorigenesismentioning
confidence: 99%